2004
DOI: 10.17660/actahortic.2004.639.29
|View full text |Cite
|
Sign up to set email alerts
|

Does Plant Color Affect Emotional and Physiological Responses to Landscapes?

Abstract: Research has shown that people have distinct preferences for and positive emotional responses to trees with a wide canopy. This is the same shape that trees have in regions of Africa's savannas with appropriate water for human habitation. Tree color is another important cue to habitats that are appropriate for human habitation. For example, nutrient deficient trees would appear yellowish. This paper covers the results of the first phase of a research study designed to test whether people have distinct preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 15 publications
5
37
0
Order By: Relevance
“…Quantitative measurement of colour will allow this property to be measured and managed, for example by setting benchmarks. Plant colour is also a trait of interest to other disciplines such as environmental psychology, where plant colour has been shown to elicit affective and cognitive responses in individuals [47]. As such, quantitative methods for measuring plant colour are likely to be of broad interest to researchers across a variety of disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative measurement of colour will allow this property to be measured and managed, for example by setting benchmarks. Plant colour is also a trait of interest to other disciplines such as environmental psychology, where plant colour has been shown to elicit affective and cognitive responses in individuals [47]. As such, quantitative methods for measuring plant colour are likely to be of broad interest to researchers across a variety of disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Also, while studies of the restorative properties of mundane nature with leafless trees have not been reported, Kaufman and Lohr (2004) found that people had more positive emotional responses to trees with foliage colors that suggested better health. Based on this, I expected views of leafless trees to be perceived as somewhat less restorative.…”
Section: The Present Studymentioning
confidence: 91%
“…The importance of flower size, the proportion of canopy covered by flowers, leaf width and leaf colour to the prediction of preference for most (but not all) people is generally consistent with other research. Specifically, research has shown that green is a preferred foliage colour (Kaufman & Lohr, 2004, that only some people prefer grey foliage (Kendal et al, 2008), that people prefer broader leaves (Williams, 2002), and that foliage colour can be an important factor in consumers' plant choices (Berghage & Wolnick, 2000;Townsley-Brascamp & Marr, 1994). The importance of flower and leaf characteristics is not surprising given the emphasis of these characteristics in horticultural plant breeding (Hobhouse, 2002), and it is likely that preferences may be an important reason plants are selected for these traits.…”
Section: A Trait-based Approach To Exploring Landscape Preferencementioning
confidence: 99%
“…This study uses objective measures of plant traits to explore the relationship between preferences and the plants in people's gardens, an approach which will allow our results to be objectively compared with results from other places. Plant traits that have been related to people's preference in garden and non-garden contexts include leaf and flower colour and size (Kaufman & Lohr, 2004Kendal, Williams, & Armstrong, 2008;Todorova, Asakawa, & Aikoh, 2004;Townsley-Brascamp & Marr, 1994), leaf width (Williams, 2002), the provision of shade or fruit (Fraser & Kenney, 2000), tree canopy shape (Lohr & Pearson-Mims, 2006;Sommer & Summit, 1995;Williams, 2002) and nativeness (Williams, 2002). This study will explore the role of preference in people's garden plant choices by focussing on plant traits including flower size, leaf colour, nativeness and leaf width.…”
Section: Introductionmentioning
confidence: 99%